TRANSITIVITY ANALYSIS OF TENTH GRADE STUDENTS’ DESCRIPTIVE TEXT - Nur Rohmat; Nurhaeni Nurhaeni; Anita Anggraeni (PROJECT (Professional Journal of English Education), 2018)
The objective of the research is to investigate the use of transitivity process in students' descriptive text and to find out the most dominant process of transitivity used. The data analyzed were 46 clauses taken from descriptive text written by six students of tenth grade of senior high school. In this research, the writers used descriptive qualitative method. The result of the research showed that there were 4 types of processes that occurred in the data, they were: material process (8, 70%), mental process (17, 39%), relational process (45, 65%), and existential process (28, 26%). While, behavioral and verbal process were not found. The most dominant process found was relational process. It implies that students were aware how descriptive text should be written, since one of language features in descriptive text is using clauses with relational process.